AB1119-HPR Evaluation of The Podiatric Need of People with Inflammatory Arthritis in Singapore. (15th July 2016) - Carter, K.; Lahiri, M.; Cheung, P.; Santosa, A.; Rome, K.
Abstract : Background: Foot problems are common in people with inflammatory arthritis [1]. International guidelines recommend referral to podiatry of all people with rheumatic disease and foot problems [2–4]. Areas covered in the guidelines include access to foot care, assessment and review, foot orthoses and footwear. It is known that access to podiatry services varies between, and even within, countries [5, 6]. Such information relating to access and uptake to podiatry services in Singapore for people with inflammatory arthritis is not available. Objectives: To assess the referral rate from a hospital rheumatology department to podiatry services, and the level of satisfaction of referred patients with their podiatry assessment and interventions. Methods: People with inflammatory arthritis were recruited from the rheumatology outpatient clinic of a large public hospital in Singapore. Disease and clinical characteristics were recorded. Participants were asked questions relating to foot problems, access to podiatry services and their perceived usefulness of foot assessment and/or interventions in alleviating their foot symptoms. A footwear assessment was also conducted. Results: 101 patients with inflammatory arthritis were recruited, of which 50% were female. The mean age was 52±15 years, and the mean disease duration was 9.3±0.3 years. The majority (86%, n=78) of participants with foot problems had discussed their foot symptoms with their rheumatologist, though only 21% of participants (n=21) were referred to a podiatrist. Of these, most (n=17, 81%) reported the foot assessments and the podiatric interventions as having been useful (n=15, 71%); 13 (62%) had been prescribed foot orthoses, of which only 9 reported finding them to be beneficial in reducing foot pain. Over 50% of all the study participants (n=51) reported problems with footwear. Only 32 people had correctly fitting footwear. No participants had been issued with therapeutic footwear. Conclusions: Though the majority of people with inflammatory arthritis reported foot problems few received a referral to podiatry. This study is the first to identify an unmet need in Singapore in the podiatric treatment of foot problems in people with inflammatory arthritis, and the under utilization of podiatry service. The results provide a foundation for further study to identify and provide solutions to overcome barriers preventing the utilization of podiatry services. References: Brenton-Rule A, et al. J Foot Ankle Res 2014; 7:36. Gossec L, et al. Joint Bone Spine 2006; 73:396–402. Forestier R, et al. Joint Bone Spine 2009; 76:691–698. National Institute of Clinical Effectiveness 2013. [http://www.nice.org.uk/Guidelines/CG79 ] Rome K, et al. NZ Med J 2013; 126:70–77. Williams A, Bowden A. Foot 2004; 14:154–158. Disclosure of Interest: None declared